2014
DOI: 10.1371/journal.pone.0088304
|View full text |Cite
|
Sign up to set email alerts
|

Wall Shear Stress Effects on Endothelial-Endothelial and Endothelial-Smooth Muscle Cell Interactions in Tissue Engineered Models of the Vascular Wall

Abstract: Vascular functions are affected by wall shear stresses (WSS) applied on the endothelial cells (EC), as well as by the interactions of the EC with the adjacent smooth muscle cells (SMC). The present study was designed to investigate the effects of WSS on the endothelial interactions with its surroundings. For this purpose we developed and constructed two co-culture models of EC and SMC, and compared their response to that of a single monolayer of cultured EC. In one co-culture model the EC were cultured on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 68 publications
1
26
2
Order By: Relevance
“…At QM15, the expression of all three proteins reached maximum values and then leveled off, suggesting that the SMCs differentiated to a contractile state. This observation is different from those of other previous studies using a similar co-culture model with SMCs cultured in collagen gel, but which did not control the phenotype of cells [13,14].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At QM15, the expression of all three proteins reached maximum values and then leveled off, suggesting that the SMCs differentiated to a contractile state. This observation is different from those of other previous studies using a similar co-culture model with SMCs cultured in collagen gel, but which did not control the phenotype of cells [13,14].…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in agreement with our previous study [9] and indicates that a physiological level of SS could maintain the contractile phenotype of SMCs co-cultured with ECs. Previous studies using an EC-SMC co-culture model mainly focused on cellular behavior under an SS of no greater than 1 Pa [5,13,14,16]. However, SMC responses to high SS are also important during initiation of cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that Cx43 was increased in ECs cultured alone by high laminar shear stress (15 dyn/cm 2 ) compared to static conditions [19,37]. However, in the present study we found that shear stress of 5 dyn/cm 2 not 12 dyn/cm 2 increased the level of Cx43 compared to static conditions in HCAECs co-cultured with HCASMCs, supported by the findings that shear stress of 4 dyn/cm 2 induced a higher Cx43 expression in ECs co-cultured with SMCs compared to ECs cultured alone [22]. In case of Cx40, a previous study showed that its endothelial protein expression was elevated markedly by shear stress from 6-10 dyn/cm 2 , while higher shear stress did not affect the expression of Cx40 in HUVECs cultured alone compared to static conditions [20].…”
Section: Discussionsupporting
confidence: 78%
“…In addition, endothelial Cx43 and Cx40, but not Cx37, demonstrated mechanosensitivity to shear stress [19,20]; thus, Cx43 distribution on the endothelium surface was changed in response to shear stress [21]. A recent study revealed that shear stress at low levels (4 dyn/cm 2 ), but not at high levels (12 ), upregulated Cx43 expression in human umbilical vein ECs (HUVECs) co-cultured with HUVSMCs, and induced HUVEC inflammatory phenotype [22]. Overall, these findings suggest that the exposure to shear stress of ECs co-cultured with SMCs may regulate SMC phenotype switching, and the formation of myoendothelial gap junctions may play a pivotal role in the process.…”
Section: Introductionmentioning
confidence: 99%
“…In an engineered vascular wall model composed of either ECs or an ECs and SMCs co-culture, wall-exerted shear stress induced ECs interactions to become less continuous. However, this effect was reduced in the co-culture construct, suggesting that EC responsiveness to wall shear stress is influenced by the presence of SMCs [54]. Fluid flow applied on ECs embedded in fibrin gels within a microfluidic device, resulted in cytoskeleton reorganization and activation of nitric oxide synthesis [55].…”
Section: External Forcesmentioning
confidence: 99%